The Optimal Permeation of Cyclic Boronates to Cross the Outer Membrane via the Porin Pathway - Gian Marco Tuveri; Matteo Ceccarelli; Alessandro Pira; Igor V. Bodrenko (Antibiotics, 2022)
We investigated the diffusion of three cyclic boronates formulated as beta-lactamase inhibitors through the porin OmpF to evaluate their potential to cross OM via the porin pathway. The three nonbeta-lactam molecules diffuse through the porin eyelet region with the same mechanism observed for beta-lactam molecules and diazobicyclooctan derivatives, with the electric dipole moment aligned with the transversal electric field. In particular, the BOH group can interact with both the basic ladder and the acidic loop L3, which is characteristic of the size-constricted region of this class of porins. On one hand, we confirm that the transport of small molecules through enterobacter porins has a common general mechanism; on the other, the class of cyclic boronate molecules does not seem to have particular difficulties in diffusing through enterobacter porins, thus representing a good scaffold for new anti-infectives targeting Gram-negative bacteria research.